Pergeseran Pola Keberagamaan Masyarakat Desa Tahunan Jepara di Era Digital - Sukarman (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
This research is descriptive study with a qualitative approach to the phenomenon of changes in religious and social patterns in the Jepara Annual village community as a result of the digital era which is marked by the development of information technology. This research uses data collection methods with observation, interviews and documentation techniques. Triangulation is used to maintain the validity of the data. Research subjects included teenagers, adults and parents. Data is processed by selecting data, synthesizing, searching and finding patterns, until finding the important meaning and what is learned. The findings from this research are that there are several socio-religious activities of the Tahunan village community that are experiencing changes. The significant shift that occurred was in the majlis ta'lim and khotmil qur'an, which were originally offline-based activities have become online-based. The advantage of this change is the efficiency of time and energy, but the disadvantage is that people's mindset tends to be pragmatic.